Desmame precoce e a suplementação com alimentos concentrados de cordeiros e seu efeito sobre as características morfológicas da pastagem e o consumo de forragem - Silva, Marina Gabriela Berchiol da [UNESP]; Monteiro, Alda Lúcia Gomes; Fernandes, Sergio Rodrigo; Silva, Cláudio José Araújo da; Cruz, Thiago Augusto; Salgado, Jordana Andrioli; Kowalski, Luciana Helena; Costa, Ciniro [UNESP] (My University, 2012)
The characteristics of the pasture and their relation to forage intake determine the responses in animal performance in finishing systems on pasture. The objective of this study was to evaluate early weaning and concentrate supplementation effects on the characteristics of the pasture and forage intake in pasture of Tifton-85 (Cynodon spp.). A randomized block design was used with four treatments, three replications and five lambs per replicate test. A total of 60 Suffolk lambs, with 36 females and 24 males were used. The treatments corresponded to the combinations between early weaning and concentrate supplementation strategies, which resulted in the following finishing systems: 1) lambs kept with mothers without supplementation; 2) lambs kept with mothers supplemented with concentrate in creep feeding at 45 ± 5 days; 3) weaned lambs at 45 ± 5 days without supplementation and 4) weaned lambs at 45 ± 5 days and supplemented with concentrate. Weaning influenced the morphological characteristics of the pasture, such as the stem mass. The results of forage intake assessment indicated that weaning affects the variables that describe the process of grazing, except for bite mass and speed of intake. It is concluded that the finishing of early weaned lambs in pasture causes changes in the characteristics of the pasture, may limit forage intake and consequently animal performance.

As características da pastagem e suas relações com o consumo de forragem determinam as respostas em desempenho animal nos sistemas de terminação em pastagem. O objetivo deste trabalho foi avaliar o desmame precoce e a suplementação com alimentos concentrados e seu efeito sobre as características da pastagem e o consumo de forragem de cordeiros em pastagem de Tifton-85 (Cynodon spp.). O delineamento foi em blocos casualizados com quatro tratamentos, três repetições, e cinco cordeiros testes por repetição. Foram utilizados 60 cordeiros Suffolk, sendo 36 fêmeas e 24 machos não castrados. Os tratamentos corresponderam às combinações entre as estratégias de desmame precoce e de suplementação com alimentos concentrados, que resultaram nos seguintes sistemas de terminação: 1) cordeiros terminados ao pé da mãe e não suplementados; 2) cordeiros terminados ao pé da mãe e suplementados com concentrado em creep feeding com início aos 45+/-5 dias; 3) cordeiros desmamados aos 45±5 dias e não suplementados; 4) cordeiros desmamados aos 45±5 dias e suplementados com concentrado. O desmame influenciou as características morfológicas da pastagem, como a massa de colmos. Os resultados obtidos na avaliação do consumo de forragem indicaram que o desmame afetou as variáveis que descrevem o processo de pastejo, exceto para massa do bocado e velocidade de ingestão. Conclui-se que a terminação de cordeiros desmamados precocemente em pastagem ocasiona modificações nas características morfológicas da pastagem, podendo limitar o consumo de forragem.
Early weaning of lambs and concentrate supplementation and its effect on morphological characteristics of the pasture and forage intake
Keywords: Concentrate supplements; Leaf: stem ratio; Nursing; Tifton-85; Aleitamento; Relação folha:colmo; Suplemento concentrado; Tifton-85